A Decade of Exploration of Transition-Metal-Catalyzed Cross-Coupling Reactions: An Overview - Kumar, Saurav; Jyoti, Jyoti; Gupta, Deepak; Singh, Gajendra; Kumar, Anil (SynOpen, 2023)
During the previous couple of decades, transition-metal (Fe, Co, Cu, Ni, Ru, Rh, Pd, Ag, Au) catalyzed inter- and intramolecular coupling reactions have attracted huge attention for the construction of C–C and C–heteroatom (like C–N, C–P, C–O, C–S, etc.) bonds to synthesize a diverse range of polymers, fine chemicals, and agrochemicals (mainly fungicides, herbicides, and insecticides), as well as biologically and pharmaceutically important organic molecules. Furthermore, the employment of lower cost and easily available metals such as first-row transition-metal salts or metal complexes of Fe, Co, Cu, Ni as catalysts compared to the precious metals such as Pd, Ag, Au in cross-coupling reactions have led to major advances in applications within the fields of synthesis. A number of cross-coupling reactions catalyzed by transition metals have been explored, including Suzuki, Heck, Sonogashira, Stille, Kumada, Kochi, Murahashi, Corriu, and Negishi reactions, as well as carbonylative, decarboxylative, reactions and α-arylations. In this review, we offer a comprehensive summary of the cross-coupling reaction catalyzed by different transition metals from the year 2009 to date.1 Introduction2 Pd-Catalyzed Reactions2.1 C–C Cross-Coupling Reactions2.2 C–N Cross-Coupling Reactions2.3 C–P Cross-Coupling Reactions3 Ni-Catalyzed Cross-Coupling Reactions3.1 C–C Cross-Coupling Reactions4 Cu-Catalyzed Cross-Coupling Reactions4.1 C–C Cross-Coupling Reactions4.2 C–O Cross-Coupling Reactions4.2 C–N Cross-Coupling Reactions4.4 C–P Cross-Coupling Reactions4.5 C–Se Cross-Coupling Reactions4.6 C–S Cross-Coupling Reactions5 Fe-Catalyzed Reactions5.1 C–C Cross-Coupling Reactions5.2 C–S Cross-Coupling Reactions6 Co-Catalyzed Reactions7 Transition-Metal Nanoparticle-Promoted Reactions7.1 Pd Nanoparticles7.2 Cu Nanoparticles8 Miscellaneous Reactions9 Perspectives and Future Directions
Keywords: cross coupling; transition metals; catalysis